Contamination Parts and Residue Levels of Multi-Mycotoxins in Medicinal and Edible Locust - Kong, Dandan (Front Pharmacol, 2018)
Locust is esteemed as a traditional Chinese medicine, as well as one of the most important nutritional foods especially in Asian countries. However, some toxic secondary metabolites such as mycotoxins are usually found in different parts of locust to affect its quality and safety. This study aimed to investigate the aflatoxins (AFs) contaminated parts by observing Aspergillus flavus, spores’ diameter, amount and distribution on head, tentacle, wing, belly and shank parts of the locust with scanning electron microscopy (SEM). Furthermore, to assess the residue levels of multi-mycotoxins in the locust, the high performance liquid chromatography with fluorescence detection (HPLC-FLD) was adopted. The technique was used to determine the contents of AFs, zearalenone (ZON) and α-zearalenol (α-ZOL) in locust and the positive samples were confirmed by high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). The chromatographic conditions, MS/MS parameters and the method of sample extraction were carefully optimized. Results revealed that obvious differences of Aspergillus flavus strains and spores were found, while the spores’ diameter ranged from 3.0 to 13.0 μm in different contaminated parts of the locust samples. The HPLC-FLD method for multi-mycotoxins analysis showed good selectivity, linearity, recovery and precision. Limits of quantification (LOQs) were lower than 27.6 μg/kg, while limits of detection (LODs) were in the range of 0.02–8.6 μg/kg. The accuracy of the developed method was validated regarding recoveries of 80.1–118.1% with relative standard deviation (RSD) ≤ 11.4%. Finally, the developed multi-mycotoxin method was applied for screening of these mycotoxins in 11 commercial locust samples. Only AFB(1) and AFB(2) were found in six samples, and the contamination levels ranged from 0.12 to 4.4 μg/kg, which were lower than the maximum residue limit and can be used safely. This is the first report on the exploration of contamination parts and levels of multi-mycotoxins in medicinal and edible locust. The combined method of SEM and HPLC-FLD exhibited advantages of low cost, high sensitivity, rapid determination, convenience and especially intuitive judgment, which is proposed for contamination parts observation, for the large-scale quantification of multi-mycotoxins in other medicinal animal matrices.